Application of Reward and Punishment in Tahfidz Quran Learning - Imron Fauzi; Maya Aniqotul Himmah (Journal of Islamic Education Research, 2022)
This study aims to describe the forms of reward and punishment, the factors supporting and inhibiting the application of reward and punishment, and the impact of applying reward and punishment in the learning of tahfidz Alquran at TPQ Darul Qur’an MSA Rogojampi Banyuwangi. This research uses a qualitative case study approach. The data analysis used in this study is a qualitative analysis of the Miles and Huberman model. To test the validity of the data obtained, the researchers used to source and technical triangulation. The study results show that: 1) The forms of application of reward that are applied are verbal and non-verbal. Punishment in the form: of light, moderate, and severe punishment. 2) factors supporting the application of rewards and punishments are the intention and enthusiasm of the students, the teacher’s participation in memorizing at least juz 30, encouragement given by parents, and positive activities in the community. The inhibiting factors are laziness, joking when learning, teachers’ absence, and parents not accepting their children being punished. The development of science and technology 3) The positive effects of reward and punishment include increased enthusiasm, motivation, responsibility, and discipline. The negative impact of applying the reward is envy. The negative impact of punishment is that it causes fear, shame, and lack of confidence and reduces the courage of students.